2012
DOI: 10.4236/ajac.2012.36055
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of HPLC Method for Simultaneous Determination of Amlodipine, Valsartan, Hydrochlorothiazide in Dosage Form and Spiked Human Plasma

Abstract: A simple, sensitive, and specific method was developed for simultaneous determination of Amlodipine besylate (AML), Valsartan (Vals) and Hydrochlorothiazide (HCT) by high performance liquid chromatography without previous separation. Satisfactory resolution was achieved using a RP-C18 chromatographic column, Phenomenex Kinetex (150 mm × 4.6 mm i.d) and a mobile phase consisting of acetonitrile-phosphate buffer (0.05 M) with pH 2.8 in the proportion of (40/60, v/v) at a flow rate 0.8 mL/min and the wavelength d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Previously described methods for determination of VAL (18)(19)(20) and CAN (21,22) in dosage forms were employed, with minor modifications. It was confirmed that the method was specific and accurate in the presence of syrup components.…”
Section: Analysis Of Drug Concentrationmentioning
confidence: 99%
“…Previously described methods for determination of VAL (18)(19)(20) and CAN (21,22) in dosage forms were employed, with minor modifications. It was confirmed that the method was specific and accurate in the presence of syrup components.…”
Section: Analysis Of Drug Concentrationmentioning
confidence: 99%
“…The derivative spectroscopy has also been applied for the determination of amlodipine and its photodegradant compound [8]. Chromatographic methods have been used widely for the analysis of AML, including thin layer chromatography (TLC) methods [9][10][11][12] and HPLC methods [13,14]. Capillary electrophoresis methods were also used for the analysis of AML in its formulations and biological fluids [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In combination with other drugs rosuvastatin has been determined by HPLC [17][18][19], chemometry in the presence of its degradation product [20].…”
Section: Introductionmentioning
confidence: 99%